Mapping Celso Pereira de Sá: Itineraries of his Intellectual Activity (1970-1990) - Garcia Alves, Roberta; Lopes Miranda, Rodrigo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
This proposal is characterized as a historical-conceptual research that aimed to identify publications of Celso Pereira de Sá linked to Behavior Analysis and to interpret conceptual and philosophical networks contained in these works, relating them to historiographical elements of his intellectual activity between 1970 and 1990. The methodological path was organized into two dimensions; one historiographic which used analysis of primary sources and another conceptual which have used Iramuteq software and appropriations of strategies of the Contextual Text Interpretation Procedure (PICT). We found an author reflecting upon the role of the intellectual and the production of scientific knowledge for solving eminently Brazilian social problems. Sá invested in popular political education in which the population would itself be able to produce knowledge about its reality and intervene in it. His concept of behavior is based on the understanding that the subject is necessarily a historical, social and verbal being. In addition, the concept of social counter-control indicates a transformation in society, highlighting the role of verbal behavior as a potential vehicle in the mobilization for social transformation.